Prevention of Physical Risk and Rehabilitation of Muscle Injury in Sanda Competition - Yong Wang (Hindawi-Wiley, 2022)
The Target. The purpose of this study is to explore the reduction of sports injury risk and verify the effective methods and means of athlete's muscle injury rehabilitation. Methods. In this study, 80 sanda athletes from a university were randomly selected as subjects, and the main parts of injury of all subjects were counted. After 12 weeks of muscle injury rehabilitation intervention, the pain, acute injury, and technical and tactical evaluation levels of subjects in the intervention group and the control group were compared. Results/Discussion. The overall performance of the 80 subjects' basic exercise ability was at a moderate level, and there was no significant difference between male and female subjects (P >0.05). After 12 weeks of rehabilitation intervention, there was no significant difference in the scores of shoulder joint flexibility, supine straight leg raising, and trunk stable support between male and female subjects in the intervention group in more than 7 sports (P >0.05). In the control group, there were significant differences in the scores of shoulder flexibility and trunk stability of male and female subjects (P<0.05). Future research should further explore the effect of muscle injury rehabilitation on effectively reducing potential sports injuries and introduce advanced and effective medical rehabilitation methods.